Relations between Benthic Diatom Community and Characteristics of Karst Ponds in the Alpine Region of Slovenia - Katarina Novak (MDPI AG, 2021)
The aim of this research was to investigate the structure of the benthic diatom community and its relations to selected environmental parameters. We collected samples in 16 karst ponds in the alpine region of Slovenia, where the Alpine karst is found. Since the predominating substrate in these ponds was clay, the epipelic community was analyzed. Hydromorphological characteristics, and physical and chemical conditions were also measured at each site. We found 105 species of diatoms, which belonged to 32 genera. The most frequent taxa were Gomphonema parvulum (Kützing) Kützing, Navicula cryptocephala Kützing, Sellaphora pupula (Kützing) Mereschkowsky (species group) and Achnanthidium pyrenaicum (Hustedt) Kobayasi. The pond with the lowest diversity was found at the highest altitude, while, on the other hand, the most species-rich pond was found at the lowest altitude. Regarding the ecological types, the most common were motile species. We confirmed a positive correlation between the number of diatom species and the saturation of water with oxygen, while correlation between species richness and NH4-N was negative. The content of NO3-N and NH4-N explained almost 20% of the total variability of diatom community. Unlike our expectations, we calculated a negative correlation between the diversity of macroinvertebrates and diatoms, which is probably a consequence of different responses to environmental conditions.